(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In opposition to the spread of gestational surrogacy as a new reproductive practice and women’s labor, this essay examines the limitations of the feminist idea of commercialization of women’s bodies. Surrogacy should be prohibited, according to feminist academics and activists, in order to preserve the unitarily of motherhood and women’s dignity. This theoretical viewpoint obscures women’s decision-making process to participate in free activities, which may be harmful to the female subject’s and other people’s well-being, by thinking that surrogates are victims of imbalanced power relations. In reality, so-called liberal feminists who support legalization and regulation of the practice believe that women should have complete choice over how they utilize their bodies and reproductive potential. In this essay, I propose reclaiming the need to safeguard the kid as the only subject with "no choice" by recognizing surrogates’ agency, positing them as subjects of social activities, and reclaiming the need to protect the child as the only subject with "no choice".